2012
DOI: 10.4103/0255-0857.99487
|View full text |Cite
|
Sign up to set email alerts
|

Presence of CTX gene cluster in environmental non-O1/O139 Vibrio cholerae and its potential clinical significance

Abstract: The emergence of a single environmental isolate in our study containing the pathogenicity genes amongst the diverse non-pathogenic environmental isolates needs to be further studied in the context of V. cholerae pathogenicity sero-coversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Other investigators have reported that environmental non-O1/non-O139 V. cholerae isolates generally do not produce cholera toxin (40,41), even though V. cholerae O1 and O139 strains isolated from the aquatic environment have been found to produce toxin (12). The transfer of cholera toxin genes to non-O1/non-O139 strains in the aquatic environment can be mediated by generalized transduction via CTX⌽ (42), and environmental vibriophages have been demonstrated to transfer toxin genes from CTX⌽-positive strains to environmental non-O1/non-O139 V. cholerae isolates (43).…”
Section: Discussionmentioning
confidence: 98%
“…Other investigators have reported that environmental non-O1/non-O139 V. cholerae isolates generally do not produce cholera toxin (40,41), even though V. cholerae O1 and O139 strains isolated from the aquatic environment have been found to produce toxin (12). The transfer of cholera toxin genes to non-O1/non-O139 strains in the aquatic environment can be mediated by generalized transduction via CTX⌽ (42), and environmental vibriophages have been demonstrated to transfer toxin genes from CTX⌽-positive strains to environmental non-O1/non-O139 V. cholerae isolates (43).…”
Section: Discussionmentioning
confidence: 98%
“…cholerae O1) including TCP and CT (Sack et al ., 2004). It has repeatedly been observed that NOVC strains may carry major virulence genes, such as those that encode for CT and TCP (Rivera et al ., 2001; Bakhshi et al ., 2012; Madhusudana and Surendran, 2013); such strains are diarrhoeagenic in humans and, theoretically, have epidemic potential (Crump et al ., 2003).…”
Section: Potential Role Of Novc In the Emergence Of New Pathogenic St...mentioning
confidence: 99%
“…V. cholerae can affect human heath, because these V. cholerae harbored virulence genes (Bakhshi et al, 2012). Infection of these V. cholerae isolates can cause watery diarrhea in humans as previously reported (Baker-Austin and Oliver, 2018).…”
Section: Phenotype and Genotype Of Amr Virulence Genes And Esbl Produ...supporting
confidence: 57%